The Fluoridation Movement and Appleton - Van Vlack, Laura (My University, 2009)
In Appleton, Wisconsin, in 1957 a battle raged over fluoridation in the water. Fluoride had been present in Appleton's water supply since 1950, when the city council voted to put it there. It came to a referendum in 1957, when local antifluoridationists called for a vote. The benefits, profluoridationists argued, were that it slowed dental decay. Opponents to fluoride, however, believed a multitude of things about fluoride. They believed it was harmful, that it would build up over time and create illnesses such as cancer. Antifluoridationists also argued that it was a poison; some political extremists even believed it to be a Communist plot to deaden American's minds and subject them to mind control. Less extreme opponents argued that it was mass medication, and an abuse of governmental power. The most common argument was that it had not yet been fully tested on adults, and therefore was not ready for public use. We will look at these sides of the opponent's arguments in Appleton, how they fit into national norms, how profluoridationists overcame their arguments and won the referendum, becoming the first city in the state of Wisconsin to keep fluoride in their water supply when it was already present.
Keywords: Water--Fluoridation--Political aspects; Water--Fluoridation--Wisconsin--Appleton; Appleton (Wis.)--History